Strategic improvement of second and third harmonic generation in multifunctional Cu-Sn-S3 ternary semiconducting thin films. (December 2019) - Acharya, B. Sudarshan; Anusha,; Antony, Albin; Ani, Aninamol; Kityk, I.V.; K.Ozga,; Slezak, A.; Jedryka, J.; Poornesh, P.; Manjunatha, K.B.; Acharya, Shashidhara
Highlights: THG and SHG signals show substantial changes in a different combination of Sn and S. Raman phonon modes were identified to dominant "A" symmetry modes. X-Ray diffraction reveals tetragonal crystal structure with (1 1 2) preferential growth orientation. Abstract: We propose a low-cost approach for the synthesis of multifunctional CuSnS3 (CTS) ternary compound thin film via spray pyrolysis technique. By varying Sn and S doping concentrations, a high energy absorber layers of CuSnS3 thin films were deposited on a glass substrate at a substrate temperature of 405 °C. The prepared samples were analysed with respect to their optical, structural and electrical and nonlinear optical properties. X-Ray diffraction (XRD) analysis reveals that the films exhibit a tetragonal crystal structure with a preferential growth orientation along (1 1 2). The surface morphology of the films was explored by atomic force microscopy (AFM) in tapping mode configuration. Variation in the carrier charge density and electrical properties were observed for different Sn and S combination. The analysis of the Raman spectra indicates the presence of multiple phases apart from CuSnS3 . The obtained Raman spectra were assigned to phonon mode as per zone centre phonon representation of optical and acoustic modes and identified to dominant "A" symmetry modes. The maximal laser stimulated induced second harmonic generation (SHG) signal was observed for the CTS 3 film and the corresponding second order nonlinear optical susceptibility which was equal to about 0.89 pm/V at 1064 nm and the minimal SHG signal was found for the CTS 2 film (about 0.22 pm/V). This strategic improvement in SHG and third harmonic generation (THG) signal efficiency endorses the role of Sn and S in modulating second and third harmonic generations in CuSnS3 compound.